Sustainable nutrition and mental health in older adults: the interplay of DASH diet quality, sustainable consumption behavior, cognitive function, and depression - Acik, Murat; Yilmaz, Birsen (Bmc, 2026)
Background & objective The global aging trend highlights the need for effective strategies to prevent cognitive impairment and depression. This study aimed to examine the mediating role of DASH diet quality in the association between sustainable dietary behaviors, cognitive function, and depressive symptoms among older adults. Methods A cross-sectional study was conducted at Firat University Hospital, involving 773 older adults. Data collection included structured questionnaires assessing demographic characteristics, DASH diet adherence (DASH Diet Quality Scale), sustainable nutritional behavior (Sustainable Consumption Behavior-Nutrition Scale, SCBN), depressive symptoms (Geriatric Depression Scale-15, GDS-15), and cognitive performance (Standardized Mini-Mental State Examination, SMMSE). Anthropometric measurements were also obtained. Statistical methods involved hierarchical regression analyses, and structural equation modeling (SEM) to examine direct and indirect relationships among study variables. Results Correlation analyses indicated negative associations between depression and both DASH diet (r= -0.378, p < 0.001) and sustainable nutritional behaviors (SCBN; r= -0.277, p < 0.001). Cognitive function positively correlated with DASH (r = 0.277, p < 0.001) and SCBN scores (r = 0.295, p < 0.001). Hierarchical regression revealed that better adherence to DASH diet (beta=-0.13, p < 0.001) and higher SCBN scores (beta=-0.12, p < 0.001) predicted lower depression scores, whereas SCBN positively predicted cognitive function (beta = 0.03, p < 0.001). Structural equation modeling confirmed that the DASH diet partly explained the association between sustainable nutrition and both depression (indirect beta=-0.02, p < 0.001) and cognitive function (indirect beta = 0.01, p < 0.001). Conclusions The study highlighted the beneficial role of DASH diet adherence and sustainable nutritional practices in mitigating depressive symptoms and supporting cognitive function in older adults. These dietary patterns could represent crucial components of preventive strategies for healthy aging. Further longitudinal research using objective dietary assessments is needed to clarify causal relationships.
Keywords: DASH diet; Sustainable nutrition; Mental health; Older adults